2017
DOI: 10.1021/acs.langmuir.7b01566
|View full text |Cite
|
Sign up to set email alerts
|

Attraction between Opposing Planar Dipolar Polymer Brushes

Abstract: We use a field theory approach to study the effects of permanent dipoles on interpenetration and free energy changes as a function of distance between two identical planar polymer brushes. Melts (i.e., solvent-free) and solvated brushes made up of polymers grafted on nonadsorbing substrates are studied. In particular, the weak coupling limit of the dipolar interactions is considered, which leads to concentration-dependent pairwise interactions, and the effects of orientational order are neglected. It is predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Explicitly, ϵ l = 1 + 4 πl Bo p 2 ρ b /3, where l Bo = e 2 /4 πϵ o k B T is the Bjerrum length in the vacuum characterized by its permittivity ϵ o , electronic charge, e , and the Boltzmann constant, k B . In eq , the term proportional to the volume V is related to self-energy of dipoles and interactions among the dipoles. , In particular, free energy density , f b becomes directly proportional to the self-energy of dipoles in the limit when the number density of dipoles (ρ b ) vanishes i.e., ρ b → 0 e.g., for a dipolar gas. The logarithmic term appearing in the expression for f b results from multibody interactions among the dipoles and is plotted in Figure (a).…”
Section: Resultsmentioning
confidence: 99%
“…Explicitly, ϵ l = 1 + 4 πl Bo p 2 ρ b /3, where l Bo = e 2 /4 πϵ o k B T is the Bjerrum length in the vacuum characterized by its permittivity ϵ o , electronic charge, e , and the Boltzmann constant, k B . In eq , the term proportional to the volume V is related to self-energy of dipoles and interactions among the dipoles. , In particular, free energy density , f b becomes directly proportional to the self-energy of dipoles in the limit when the number density of dipoles (ρ b ) vanishes i.e., ρ b → 0 e.g., for a dipolar gas. The logarithmic term appearing in the expression for f b results from multibody interactions among the dipoles and is plotted in Figure (a).…”
Section: Resultsmentioning
confidence: 99%
“…However, forming these special interactions usually requires complicated chemical synthesis and processing steps to introduce specific functional groups such as hydroxyl groups into polymer chains. , Recently, strong interchain van der Waals interaction (VDW) has emerged as a promising tool to fabricate novel polymer materials with excellent performances. Using the key-and-lock interchain junction mechanism formed by favorable interchain van der Waals forces, Urban et al reported the commodity copolymers such as PMMA/ n -butyl acrylate [P­(MMA/ n BA)], and their derivatives exhibited interesting self-healing performance. Compared to the supramolecular interaction, the strong van der Waals interaction such as dipolar interaction was more easily fulfilled in the commodity polymer without complicated chemical and physical alterations. …”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [20], Mahalik et al [21], Budkov et al [22], Gordievskaya et al [23], show that the effect of dipole-dipole interaction between transverse dipoles can be described by the introduction of the macroscopic effective Flory-Huggins-like parameter which depends on the polymer concentration. These interactions can lead to the collapse of the dipolar flat brushes and to an attraction between two opposite brushes at intermediate separation distances [24]. To avoid misunderstandings, A-type brushes were not considered in these works.…”
Section: Introductionmentioning
confidence: 99%